2023
DOI: 10.3390/ijms24021786
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cancer Stem Cells as the Key Driver of Carcinogenesis and Therapeutic Resistance

Abstract: The emerging concept of cancer stem cells (CSCs) as the key driver behind carcinogenesis, progression, and diversity has displaced the prior model of a tumor composed of cells with similar subsequently acquired mutations and an equivalent capacity for renewal, invasion, and metastasis. This significant change has shifted the research focus toward targeting CSCs to eradicate cancer. CSCs may be characterized using cell surface markers. They are defined by their capacity to self-renew and differentiate, resist c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 186 publications
0
13
0
Order By: Relevance
“…[ 59 , 60 ] However, There are several drawbacks that limit the clinic applications in currently available anti-CSCs drugs and therapies, including limited solubility, low stability, high toxicity, and lack of tissue selectivity. [ 61 ] Hence, even the CSCs transformation research is not shown in our bibliometric analysis results, it is also need more attention and development.…”
Section: Discussionmentioning
confidence: 98%
“…[ 59 , 60 ] However, There are several drawbacks that limit the clinic applications in currently available anti-CSCs drugs and therapies, including limited solubility, low stability, high toxicity, and lack of tissue selectivity. [ 61 ] Hence, even the CSCs transformation research is not shown in our bibliometric analysis results, it is also need more attention and development.…”
Section: Discussionmentioning
confidence: 98%
“…Carcinogenesis is a complex process that involves several components to drive the cell from its normal state into a cancerous one [ 47 ]. CDKN2A is a gene that belongs to the category of tumor suppressor genes and the malfunction of these genes participates in tumor initiation [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The oncogene overexpression in cancerous tissues is a distinguishing feature of malignancy [ 52 ]. Therefore, in the initial stage of this study, we employed data from the Tumor Immune Estimation Resource, version 2 (TIMER2.0) [ 53 ], to visually represent the differences in RFC4 gene expression between tumor and normal tissue.…”
Section: Methodsmentioning
confidence: 99%